Oxidative balance score reflects vascular endothelial function of Chinese community dwellers - Liu, Jianhua; He, Lingxiao; Wang, Aozhe; Lv, Yuanyuan; He, Hui; Wang, Chenghao; Xiong, Kaiyu; Zhao, Li (Frontiers in Physiology, 2023)
Background: The oxidative balance score (OBS) is a composite estimate of the overall pro- and antioxidant risk status in an individual. The aim of this study is to explore the association between the OBS and vascular endothelial function in Chinese community dwellers. Methods: In total, 339 community dwelling adults (aged 20–75 years) were recruited in this study. The overall OBS was calculated on the basis of 16 pro- and antioxidant factors related to diet (measured by fasting blood samples) and lifestyle (evaluated by questionnaires). The dietary OBS and lifestyle OBS were calculated on the basis of the corresponding components. Serum iso-prostaglandin F2α (FIP) was measured to evaluate the oxidative stress degree, and brachial artery blood flow-mediated dilation (FMD) was measured for vascular endothelial function. The FIP and FMD levels were dichotomized as “low” or “high” using the corresponding median values (low FIP, n = 159; high FIP, n = 180; low FMD, n = 192; and high FMD, n = 147). The components of the OBS were compared between the stratified FIP and FMD groups. Logistic regression was used to analyze the OBS associations with FIP and FMD. Results: The higher overall OBS and dietary OBS were associated with lower FIP (p < 0.001), whereas the higher overall OBS (p < 0.01) and dietary OBS (p < 0.05) were associated with higher FMD. The lifestyle OBS was not associated with FIP and FMD (p > 0.05). Except for the body mass index (BMI) and low physical activity, all other OBS components were significantly different between the low FIP and high FIP groups (p < 0.05). Four diet-related antioxidants (α-carotene, zeaxanthin, α-tocopherol, and γ-tocopherol) showed significant differences between the high and low FMD groups (p < 0.05). Conclusion: The decreasing OBS level was associated with low endothelial function and high oxidative stress. The dietary OBS, rather than the lifestyle OBS, was more closely associated with endothelial function.